Wave dispersion in thin-walled orthotropic waveguides using the first order shear deformation theory. (June 2016) - Mazzotti, M.; Bartoli, I.; Miniaci, M.; Marzani, A.
Abstract: The aim of this paper is to extract the dispersion parameters, i.e. phase velocity, energy velocity and attenuation, of orthotropic thin-walled waveguides with generic cross-section. To this end, a semi-analytical finite element (SAFE) formulation is presented, which is based on the Reissner–Mindlin theory of curved shells. Complex axial wavenumbers and mode shapes of guided wave modes are extracted from a second-order polynomial eigenvalue problem, while the energy velocity is post-processed using the computed eigensolutions and SAFE operators. Different numerical examples are proposed, for which the obtained results are in very good agreement with those computed using other well-stated SAFE formulations. Abstract : Highlights: A SAFE formulation based on the Reissner–Mindlin theory of shells is proposed. Thin-walled waveguides with generic curved cross-section are considered. Material orthotropy and viscoelasticity are taken into account. A closed formula for the energy velocity based on SAFE operators is presented. It is shown that an axial prestress leads to a decrease of the attenuation values.